1987
DOI: 10.1203/00006450-198712000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Lamb Ventricles Respond Differently to Filling and Arterial Pressures and to in Utero Ventilation

Abstract: ABSTRACT. Right and left ventricular function were in-function curve. but differs in that it is positioned "above" the vestigated in 12 fetal lambs (127-140 days gestation) left ventricular curve. Although these experiments support the instrumented with electromagnetic flow sensors on the concept of right ventricular dominance, statistical significance ascending aorta and the main pulmonary artery, and with between the positions of the function curves was not achieved vascular catheters. Nine fetuses were equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
2

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 16 publications
8
74
2
Order By: Relevance
“…4 0 kPa(48.9 + 3.0 mm Hg), P0~2.61 + 0.25 kPa (19.6 f 1.9 mm Hg), Ca02 8.3 h 1.4 mL/dL, and hematocrit 37.5 + 6.2%. Hemodynamic parameters including heart rate, carotid artery pressure, pulmonary artery pressure, and right atrial pressure (Table I) were comparable to previously published data for chronically instrumented fetal lambs (12). Right ventricular stroke volume was defined as 100% at baseline and decreased to 52% of baseline with the maximal applied pulmonary artery pressure load.…”
Section: Resultssupporting
confidence: 67%
“…4 0 kPa(48.9 + 3.0 mm Hg), P0~2.61 + 0.25 kPa (19.6 f 1.9 mm Hg), Ca02 8.3 h 1.4 mL/dL, and hematocrit 37.5 + 6.2%. Hemodynamic parameters including heart rate, carotid artery pressure, pulmonary artery pressure, and right atrial pressure (Table I) were comparable to previously published data for chronically instrumented fetal lambs (12). Right ventricular stroke volume was defined as 100% at baseline and decreased to 52% of baseline with the maximal applied pulmonary artery pressure load.…”
Section: Resultssupporting
confidence: 67%
“…Previous studies showed that in utero oxygen ventilation creates a central circulatory pattern identical with that in the immediate postnatal period (18,19,32,33). The arterial blood gases obtained at a time when the umbilical cord was occluded support the notion that the lungs became the sole site for gas exchange.…”
Section: Volumementioning
confidence: 59%
“…It is likely that these functions play a role in a range of fetal hemodynamic phenomena, including the recognized lability of the fetal pulmonary circulation (38), the observation of a 5-8 mmHg higher systolic blood pressure in the pulmonary trunk compared with the ascending aorta (36), and the propensity of an increase in afterload to reduce fetal RV output (35,37).…”
Section: Perspectives and Significancementioning
confidence: 99%